Marriage Status in the Indonesian Islamic Da’wa Institution (LDII): A Sociology of Law Review on Nikah Dalam Tradition - Imtihanah, Anis Hidayatul; Tanzilulloh, M. Ilham; Ratnasari, Frida; Sari, Ima Frafika (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The Indonesian Islamic Da’wa Institution (LDII) has a different marriage arrangement from most. In the matchmaking process, they have a marriage team responsible for overseeing it and facilitating an unregistered marriage (nikah dalam). An unregistered marriage is a marriage contract carried out by the congregation before a marriage is performed in the Office of Religious Affairs. This study aims to analyze the matchmaking process and the unregistered marriage practice carried out by the LDII in Sawoo Village, Ponorogo, Indonesia, utilising a Sociology of Law approach and the Structural-Functional (AGIL) framework. This study employed a descriptive-qualitative approach to describe and analyze the phenomenon. The findings show that the practice of nikah dalam in the LDII community is influenced by cultural, social, biological, and personality systems. Furthermore, it is also an effort to maintain a system that has become a stable norm in the community because it meets four functional requirements. They are Adaptation, Goal Attainment, Integration, and Latency. Therefore, the system remains alive and runs well, preventing conflict. This paper contributes to studies in the Islamic Family Law, especially, regarding traditions and marriage practices in Indonesian religious organizations. This study also provides a detailed account of how religious authority acts as the primary legal actor in enforcing the community's internal rules.